Predictors of health insurance uptake among residents of Lagos, Nigeria - Olufemi Erinoso; Afolabi Oyapero; Oluwabukunmi Familoye; Adenike Omosun; Adeyinka Adeniran; Yetunde Kuyinu (Population Medicine)
Introduction Health insurance is a health-financing mechanism to protect people from catastrophic healthcare costs and limits out-of-pocket spending on healthcare, which is directly linked to poverty. This study assesses the extent of health-insurance uptake and associated factors in Lagos, Nigeria.